2021
DOI: 10.1097/cm9.0000000000001477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colloid preload on the incidence of hypotension in spinal anesthesia for cesarean section: a systematic review and meta-analysis

Abstract: Background:Hypotension is a common complication caused by spinal anesthesia (SA), which may have adverse impacts on the condition of the parturient and fetus. Liquid infusion was found to be relatively effective for reducing the incidence of hypotension. However, the question of whether colloid preload can optimize hemodynamic variables in the cesarean section remains controversial. This study aims to determine the effects of colloid preload on the incidence of hypotension induced by SA in elective cesarean se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…On the other hand, some authors noted that patients with colloid preload had fewer episodes of low blood pressure than those patients with colloid coloads ( 21 , 22 ). In other studies, both groups were similarly hypotensive ( 23 27 ). In summary, in human medicine there is still no consensus on the type of fluid and its loading time in patients undergoing EA or regarding the total fluid and dosing rate in preventing epidural hypotension.…”
Section: Introductionmentioning
confidence: 62%
“…On the other hand, some authors noted that patients with colloid preload had fewer episodes of low blood pressure than those patients with colloid coloads ( 21 , 22 ). In other studies, both groups were similarly hypotensive ( 23 27 ). In summary, in human medicine there is still no consensus on the type of fluid and its loading time in patients undergoing EA or regarding the total fluid and dosing rate in preventing epidural hypotension.…”
Section: Introductionmentioning
confidence: 62%
“…Current researchers have investigated the administration of colloid preload during neuraxial (spinal) anesthesia to see how well it can reduce the risk of hypotension during cesarean sections [ 5 ]. Gong et al found after analyzing 831 patients in a total of nine studies, that there were no significant differences in hypotension between those who received colloid preload and the control group [ 5 ]. The researchers also found that hypotension occurring during spinal anesthesia is an important factor in intra-operative nausea and vomiting due to gut ischemia and serotonin release.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers also found that hypotension occurring during spinal anesthesia is an important factor in intra-operative nausea and vomiting due to gut ischemia and serotonin release. However, there were no significant differences in hypotension levels compared to the control group when colloid was administered [ 5 ]. Additionally, when analyzing volume therapy, a rapid crystalloid co-loading is more effective in reducing the incidence of hypotension than a crystalloid preload [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…34 Hypotension often occurs after neuraxial anesthesia during cesarean section and may lead to poor prognosis for both the parturients and fetus in severe cases. 35 In theory, esketamine has a sympathetic nerve stimulating effect, 36 which can increase the heart rate and blood pressure. Therefore, it may not be suitable for Patients with gestational hypertension, preeclampsia, or eclampsia.…”
mentioning
confidence: 99%